IMPLEMENTATION OF THE JUSTICE PRINCIPLE IN CIVIL RELATHIONS - Kh. O. Ugurchiyeva (Russian Journal of Economics and Law)
This article discusses the mechanism of implementing the principle of justice in civil matters as an expression of moral principles and civil regulation. It also notes that the principle of justice is manifested in the relations of the parties civil law cases, not only in direct reference to it in law, but often implies or is present in the behavior of participants in civil relations.